Pengaruh Aksesibilitas Terhadap Keputusan Berkunjung di Chevilly Resort and Camp - Sam, Samuel; Raidah Zhafirah Febrianti (Journal of Event, Travel and Tour Management, 2024)
Accessibility is an important aspect of tourist destinations that makes it easier for visitors to travel. Accessibility also influences visitors' desire to visit tourist destinations. Easy, adequate access and connected to public infrastructure services such as gas stations, minimarkets and others will influence tourists' interest in coming. The purpose of this research is to determine the influence of accessibility on the decision to visit Chevilly Resort and Camp. This research uses quantitative methods with a sample of 109 visitors. This sampling technique uses accidental sampling. The data analysis method used is simple linear regression which includes validity test, reliability test, normality test, T test and coefficient of determination test ¬(R2). The author uses quantitative descriptive methods with data analysis using IBM SPSS Statistics 26. The research results show that accessibility influences the decision to visit with the results being 72.9% influenced by this variable and the remainder influenced by other variables not examined in this research. The conclusion is that accessibility has a significant influence on the decision to visit through the ease of access provided by the Chevilly Resort and Camp to meet visitors' travel needs.